x=1 2/3
How?:
2x-4+3 = 5x-6
2x-1 = 5x-6
2x-1+1 = 5x-6+1
2x = 5x-5
2x-5x = 5x-5x-5
-3x = -5
-3x/-3 = -5/-3
x = 5/3
x = 1 2/3
If the variable x represents the number: 5x + 3ParenthesesExponentsMultiplyDivideAddSubtractAlways remember this
You can work this out with long division, by checking to see if (x2 - 1) is a factor of (2x4 + 4x3 - x2 + 4x - 3). It is. Unfortunately, the WikiAnswers system is somewhat limited in depicting things such as long division, so we won't be able to represent it here. In short though, (2x4 + 4x3 - x2 + 4x - 3) / (x2 + 1) is equal to 2x2 + 4x - 3. which means that: (x2 + 1) / (2x4 + 4x3 - x2 + 4x - 3) = (x2 + 1) / (x2 + 1)(2x2 + 4x - 3) = 1 / (2x2 + 4x - 3)
4+1=5. Plus 4 equals 9. Plus 77685769844446473 equals 77685769844446482. Plus 3 equals 77685769844446485. Plus 8 equals 77685769844446493. Plus 1 equals 77685769844446494. Plus 9870998342523322424 equals 1064785604097768918. Plus 4 equals 1064785604097768922.
59
and the answer is 41
If there is an equals sign between the 3 and 5 of 35, then it is the associative property of multiplication.
r = 3 s = 5 t = 6 rs = 3x5 = 15 rt = 3x6 = 18 st = 5x6 = 30
No.
42
67 plus 3 equals 70.
3 plus 1 plus 4 equals 8
Yes, -8 plus plus 3 equals -5. The "plus plus" is equivalent to a positive sign, so -8 plus (+3) equals -5.
12
2.5 plus 6 plus 3 equals 2.5 plus 6 plus 3
89
2x4 - 7x3 + x2 + 7x - 3 = (x + 1)(2x3 - 9x2 + 10x - 3) = (x + 1)(x - 1)(2x2 -7x + 3) = (x + 1)(x - 1)(x - 3)(2x -1)
4 plus 3 equals 7